The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/cells12121624
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of TGF-β Signaling Pathways in Human Corneal Endothelial Cell Primary Culture

Abstract: Corneal endothelial diseases are the leading cause of corneal transplantation. The global shortage of donor corneas has resulted in the investigation of alternative methods, such as cell therapy and tissue-engineered endothelial keratoplasty (TEEK), using primary cultures of human corneal endothelial cells (hCECs). The main challenge is optimizing the hCEC culture process to increase the endothelial cell density (ECD) and overall yield while preventing endothelial–mesenchymal transition (EndMT). Fetal bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…CD166 is a basolateral transmembrane protein involved in cell-cell adhesion. NCAM is a specific endothelial marker localized on the lateral membrane of CECs [30,31].…”
Section: Immunolabeling Of Endothelial Markersmentioning
confidence: 99%
“…CD166 is a basolateral transmembrane protein involved in cell-cell adhesion. NCAM is a specific endothelial marker localized on the lateral membrane of CECs [30,31].…”
Section: Immunolabeling Of Endothelial Markersmentioning
confidence: 99%
“…In a study of corneal transplantation, TGF-β has been shown to play a crucial role in triggering the immune response that can lead to graft rejection by reducing the density of endothelial cells [192]. To address this, the authors utilized an in vitro treatment scheme with a TGF-β neutralizing antibody, fresolimumab.…”
Section: Therapeutic Targets For Tgf-β Signaling Based Therapiesmentioning
confidence: 99%
“…This treatment aimed to prevent the loss of endothelial cells by inhibiting the transition from endothelial to mesenchymal states, a process stimulated primarily by TGF-β1 and, to a lesser extent, TGF-β3. The findings highlighted that while fresolimumab effectively suppresses this transition, its efficacy varies across different TGF-β isoforms, which could influence the overall success of preventing graft rejection [192].…”
Section: Therapeutic Targets For Tgf-β Signaling Based Therapiesmentioning
confidence: 99%
“…Advanced cell culture media formulations containing growth factors, cytokines, and extracellular matrix components have been designed to support CEC proliferation while preserving cellular morphology and function. Optimized culture media contains the following components [66][67][68][69]:…”
Section: Cell Culture Media Compositionmentioning
confidence: 99%